2016
DOI: 10.1016/j.str.2015.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoatomic Structure of the Tripartite Multidrug Efflux Pump AcrAB-TolC Reveals the Intermeshing Cogwheel-like Interaction between AcrA and TolC

Abstract: The resistance-nodulation-division type tripartite pump AcrAB-TolC and its homologs are responsible for multidrug resistance in Gram-negative bacteria by expelling a wide variety of toxic substrates. The three essential components, AcrA, AcrB, and TolC, must function in concert with each respective binding partner within the complex. In this study, we report an 8.2-Å resolution cryo-electron microscopy (cryo-EM) 3D reconstruction of the complex that consists of an AcrAB fusion protein and a chimeric TolC prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
55
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 24 publications
10
55
0
Order By: Relevance
“…The increased diameter (from 13.5 to 29.0 Å) upon TolC-AcrA association, would admit the translocation of larger molecules, which is in agreement with other strong and recent experimental evidences. [17][18][19] The new proposed model also satisfied the Cryo-EM map volume described by Du et al 6 as seen in Figure 4c. Torres et al 2385 Vol.…”
Section: Resultssupporting
confidence: 69%
“…The increased diameter (from 13.5 to 29.0 Å) upon TolC-AcrA association, would admit the translocation of larger molecules, which is in agreement with other strong and recent experimental evidences. [17][18][19] The new proposed model also satisfied the Cryo-EM map volume described by Du et al 6 as seen in Figure 4c. Torres et al 2385 Vol.…”
Section: Resultssupporting
confidence: 69%
“…However, if the TriABC-OpmH complex resembles that of AcrABTolC, then in the assembled complex, the channel is in the open conformation, which is stabilized by specific interactions with MFPs ( Fig. 1C and 4C) (7,8). To investigate whether any of the disulfide bonds between MFPs and OpmH contribute to opening of the channel and prevent its closure, we measured the change in susceptibility to azithromycin, an ϳ740-Da antibiotic that does not readily permeate the outer membrane and is not a substrate of TriABC-OpmH.…”
Section: Figmentioning
confidence: 99%
“…In the resting state, the aperture of the OMF remains in a closed state and only upon functional interactions with the inner membrane components of the tripartite complex does the OMF transition into an open state, allowing efflux of substrates into the extracellular milieu (4)(5)(6)(7)(8) (Fig. 1C).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A small peptide, AcrZ, has been identified that modifies the activity of AcrB (Hobbs et al, 2012). Previous electron microscopy studies of the AcrAB-TolC pump have revealed the overall shape of the pump and the relative arrangement of its components (Daury et al, 2016; Du et al, 2014; Jeong et al, 2016). Due to the limited resolution, these studies were unable to identify the detailed interaction interfaces between the components.…”
Section: Introductionmentioning
confidence: 99%